79.2k views
1 vote
Convert to standard form 25x^2 + 4y^2 - 50x -75 = 0

User Stiefel
by
4.4k points

1 Answer

3 votes

Answer:


((x-1)^(2))/(4)+(y^(2))/(25)=1

Explanation:

we have


25x^(2)+4y^(2)-50x-75=0

Convert to standard form

Group terms that contain the same variable, and move the constant to the opposite side of the equation


(25x^(2)-50x)+4y^(2)=75

Factor the leading coefficient of each expression


25(x^(2)-2x)+4y^(2)=75

Complete the square twice. Remember to balance the equation by adding the same constants to each side.


25(x^(2)-2x+1)+4y^(2)=75+25


25(x^(2)-2x+1)+4y^(2)=100

Rewrite as perfect squares


25(x-1)^(2)+4y^(2)=100

Divide both sides by the constant term to place the equation in standard form


(25(x-1)^(2))/(100)+(4y^(2))/(100)=(100)/(100)

Simplify


((x-1)^(2))/(4)+(y^(2))/(25)=1

User Lasse Edsvik
by
4.7k points